The So-Called Old Church Slavonic Moscow Missal Marianus as a Reflection of 15th Century Lithuanian-Belorussian-Polish Cultural Relations - Moszyński, Leszek (Kalbotyra, 1997)
This paper discusses the so-called Old Church Slavonic Moscow Missal Marianus regarding its text, language and historical context. This text and its language are considered to be a reflection of the 15th century Lithuanian-Belorussian-Polish cultural relations. Thus, this unique text contains a Catholic Missal, written in Old Church Slavonic using the Cyrillic alphabet. Its language is being described as Old Church Slavonic in its East Slavic (Belorussian) version, presenting at the same time a number of loan-words from Croat and Polish. It is assumed that this literary monument was created in Krakow by transcribing a Croat glagolitic text into the Cyrillic alphabet for princess Zofia Holšańska, the primary Orthodox believer and the fourth wife of Jagielło, the Grand Duke of Lithuania and the King of Poland.